New Traveling Wave Solutions For Some Nonlinear Fractional Differential Equations By Extensions Of Basic - Ali Al-Shawba, Altaf Abdulkarem (2022)
Due to varied and important applications of nonlinear fractional differential equations in real world problems, it is often required to construct their exact analytical solutions. With the help of exact analytical solutions, if they exist, the modelled phenomena can be better understood. Generally, an important class of solutions of nonlinear evolution equations (EEs) is their travelling wave solutions.